Cost-effectiveness analysis of first-line sintilimab plus chemotherapy vs. chemotherapy alone for unresectable advanced or metastatic gastric or gastroesophageal junction cancer in China - Xiang, Zuojuan; Ma, Ling; Fu, Yingzhou; Pan, Yong (Frontiers in Pharmacology, 2024)
Background The Chinese Society of Clinical Oncology (CSCO) has recommended sintilimab plus chemotherapy (SINT+Chemo) as a standard first-line therapy for advanced gastric cancer or gastroesophageal junction cancer (GC/GEJC), based on the proven effectiveness and safety in the ORINT-16 trail. Its cost-effectiveness, however, remains to be evaluated. Methods We established a partitioned survival approach (PartSA) model with a 10-year time horizon to determine whether SINT+Chemo (vs chemotherapy) was more cost-effective as a first-line treatment for unresectable advanced or metastatic GC/GEJC. Survival data was generated from the ORIENT-16 trail. Cost calculation was limited to direct medical costs. Database of Hunan Public Resources Trading Service Platform was used as the source for obtaining drug prices. Other cost and utility values were gathered from established literature. Incremental cost-effectiveness ratio (ICER) was the primary output. Additionally, we conducted sensitivity analysis, subgroup analysis, and scenario analysis. Results In the base-case analysis, group SINT+Chemo showed an increase in utility value by 0.32 quality-adjusted life-years (QALYs) at an extra cost of $7988.43, resulting in an ICER of $25239.29/QALY, below the Chinese cost-effective willingness-to-pay(WTP) threshold of $38223.34. Upon further subgroup analysis according to patients’ programmed death 1 ligand (PD-L1) combined positive score (CPS) , the ICERs were $26341.01/ QALY for patients highly expressing PD-L1 (CPS ≥ 5) and $17658.26/QALY for patients lowly expressing PD-L1 (CPS < 5). Based on the sensitivity analysis, we found the PFS utility was the parameter that had the most significant impact on the model's outcomes. Moreover, in scenario analysis, the results remained consistent despite variations in the model's time frame. Conclusion In China, SINT+Chemo is a more cost-effective option (vs chemotherapy) as a first-line therapy for unresectable advanced or metastatic GC/GEJC, irrespective of PD-L1 expression levels.